Analysis of the impact of the margin trading system and stock market volatility in mainland China —Base on an empirical study - Ao, Xinyi (2022)
This paper focuses on the daily closing prices of the CSI 300 Index for the period from December 2013 to December 2021 as the sample data, with a total of 1,952 trading days. After testing, a GARCH (1, 1)-t distribution model is used to fit the volatility of the stock market in mainland China. A VAR model was constructed to analyse the interaction between changes in financing and financing securities and stock market volatility. Interval data were selected for testing to analyse the relationship between the variables, followed by AR root tests and impulse response analysis by identifying and estimating VAR models. The results of the study show that the margin purchase regime has a large impact on stock market volatility, although it becomes progressively smaller over time. Although the short selling regime does not have as large an impact on stock market volatility as the margin buying regime at the beginning, its impact becomes larger over time. By analysing the results of the Granger causality test, changes in margin trading are Granger causes of stock market volatility, and stock market volatility is also Granger cause of changes in margin trading. The two are mutually causal.In the case of margin trading operations, it is evident from the empirical results that the margin trading system increases the volatility of the stock market. If the margin trading system is divided into two types of trading, namely the purchase margin system and the short selling system. This paper finds that while short selling increases the volatility of the stock market, the margin buying system also increases the volatility of the stock market. Although the results of the variance decomposition show that the impact is very limited now. However, in the long run, the impact is deepening.